2008
DOI: 10.1002/jmv.21319
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of peginterferon alpha‐2a/ribavirin in treatment‐naive Cameroonian patients with chronic hepatitis C

Abstract: Data were examined from a day-to-day clinical practice in Yaounde, Cameroon to evaluate the efficacy and safety of peginterferon alfa-2a and ribavirin in treatment-naive Cameroonian patients with chronic hepatitis C. Ninety adults with chronic hepatitis C (mean age, 53 +/- 8 years; 79% males; 37.8% genotype 1; 23.3% genotype 2; and 38.9% genotype 4) were given at least 12 weeks of combination therapy between February 2003 and August 2007. Of these, 54 completed the treatment and the 24-week follow up. Subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 38 publications
(66 reference statements)
2
20
0
1
Order By: Relevance
“…These results were in agreement with the studies carried at University of Southampton [37]. Further more in both regimens HCV genotype 2, had a higher ETR than genotype 1 and 4 which same as previous study was carried in Cameroon [38]. However, both therapeutic regimens were less effective in patients infected with HCV genotype 1 and 4 although much higher ETR rates are reached in individuals infected with genotype 2.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results were in agreement with the studies carried at University of Southampton [37]. Further more in both regimens HCV genotype 2, had a higher ETR than genotype 1 and 4 which same as previous study was carried in Cameroon [38]. However, both therapeutic regimens were less effective in patients infected with HCV genotype 1 and 4 although much higher ETR rates are reached in individuals infected with genotype 2.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have shown no differences in the clinical response of patients infected with HCV genotype 2 and 3, when they were treated with PEG INF alfa2a or INF alfa combination therapies [38,39]. The SVR of Peg INF based regimen was higher than INF based Regimen in all genotypes except for genotype 4 because as 11 patient infected with this genotype had ETR of Peg INF miss the follow up and thus excluded for the data analysis.…”
Section: Discussionmentioning
confidence: 86%
“…The majority of studies (40/51, 78%) originated from the Middle East[1013, 15, 16, 18, 27, 28, 34, 35, 37, 4042, 45, 46, 53–56, 59, 62, 63, 66, 67, 69, 72, 75, 78, 80, 81, 8385, 88, 91, 95] and Europe (9/51, 18%)[14, 38, 39, 65, 71, 76, 79, 93, 96]. One originated in Cameroon[77] and one multi-center study was conducted in 19 countries[73]. Most studies were performed in a university setting and had an ITT analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Au Maroc et en Tunisie, avec une prévalence variant de 30 à 66 %, le génotype 1 est le plus fréquent [15][16][17]. Avec des taux pouvant atteindre les 13 %, l'Égypte a la prévalence la plus élevée au monde pour le génotype 4 ; génotype également prédominant au Zaïre, au Gabon, au Cameroun et en Tanzanie [18][19][20][21][22]. Dans la littérature [6,7] Anémie ≤ 9 g/dl Hémoglobine 2 (11,1) > 9 g/dl Hémoglobine 6 (33,3) Neutropénie 1 000 à 750/mm 3 11 (61,1) < 750/mm 3 6 (33,3) Thrombopénie ≤ 100 000/mm 3 2 (11,1) > 100 000/mm 3 12 (66,6) besoin d'être confirmés par des études ultérieures sur des effectifs plus importants.…”
Section: Bithérapie Interféron Pégylé-ribavirineunclassified